Magnetized Fast ignition (MFI) and Laser Plasma Interactions in Strong Magnetic Field. (March 2016) - Mima, Kunioki; Johzaki, T.; Honrubia, J.; Nagatomo, H.; Taguchi, T.; Sunahara, A.; Sakagami, H.; Fujioka, S.; Logan, G.
Abstract: In this paper, magnetized fast ignition (MFI) is proposed for improving the coupling efficiency of a heating laser to a core plasma. In the MFI, the external magnetic field is applied to reduce the hot electron energy and focus the dense hot electron flux to the core. The external magnetic field higher than 100T is generated by the laser driven coil and it is amplified by the implosion. The magnetic field at the tip of the cone is expected to reach higher than 10kT and the laser plasma interaction and the hot electron transport are modified. As the results of applying the external magnetic field, hot electron energy is reduced to less than 5MeV for the laser intensity of 10 20 W/ cm 2 and the Weibel instability is suppressed to collimate the hot electron beam to the core.